ACR Appropriateness Criteria® Intensive Care Unit Patients. Issue 6 (November 2015) - Suh, Robert D.; Genshaft, Scott J.; Kirsch, Jacobo; Kanne, Jeffrey P.; Chung, Jonathan H.; Donnelly, Edwin F.; Ginsburg, Mark E.; Heitkamp, Darel E.; Henry, Travis S.; Kazerooni, Ella A.; Ketai, Loren H.; McComb, Barbara L.; et al.
Abstract : Portable chest radiography is a fundamental and frequently utilized examination in the critically ill patient population. The chest radiograph often represents a timely investigation of new or rapidly evolving clinical findings and an evaluation of proper positioning of support tubes and catheters. Thoughtful consideration of the use of this simple yet valuable resource is crucial as medical cost containment becomes even more mandatory. This review addresses the role of chest radiography in the intensive care unit on the basis of the existing literature and as formed by a consensus of an expert panel on thoracic imaging through the American College of Radiology. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed every 3 years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer-reviewed journals and the application of a well-established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances in which evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment.